The Prognostic Values of Leukocyte Rho Kinase Activity in Acute Ischemic Stroke. (27th February 2014) - Cheng, Cheng-I.; Lin, Yu-Chun; Tsai, Tzu-Hsien; Lin, Hung-Sheng; Liou, Chia-Wei; Chang, Wen-Neng; Lu, Cheng-Hsien; Yuen, Chun-Man; Yip, Hon-Kan
Abstract : Objective . It has been reported that leukocyte ROCK activity is elevated in patients after ischemic stroke, but it is unclear whether leukocyte ROCK activity is associated with clinical outcomes following acute stroke events. The objective of this study is to investigate if leukocyte ROCK activity can predict the outcomes in patients with acute ischemic stroke. Materials and Methods . We enrolled 110 patients of acute ischemic stroke and measured the leukocyte ROCK activity and plasma level of inflammatory cytokines to correlate the clinical outcomes of these patients. Results . The leukocyte ROCK activity at 48 hours after admission in acute ischemic stroke patients was higher as compared to a risk-matched population. The leukocyte ROCK activity significantly correlated with National Institute of Health Stroke Scale (NIHSS) difference between admission and 90 days after stroke event. Kaplan-Meier survival estimates showed lower stroke-free survival during follow-up period in patients with high leukocyte ROCK activity or plasma hsCRP level. Leukocyte ROCK activity independently predicted the recurrent stroke in patients with atherosclerotic stroke. Conclusions . This study shows elevated leukocyte ROCK activity in patients with ischemic stroke as compared to risk-matched subjects and is an independent predictor for recurrent stroke.